Comparative Study of Antioxidant, Antimicrobial and a-Amylase Inhibitory Activities of Leaves, Fruits and Seeds of Carissa opaca - Ahmed, Dildar; Hammad, Muhammad (Asian Journal of Chemistry, 2013)
Carissa opaca Stapf ex Haines is a medicinal plant found in different hilly areas of Indo-Pakistan subcontinent. The present study aimed to compare antioxidant, antimicrobial and a-amylase inhibitory activities of leaves, fruits and seeds of C. opaca. The free radical scavenging activities of leaves, fruits and seeds were 89.84, 9.44 and 3.85 %. The leaves also showed much higher antioxidant activity determined by phosphomolybdate assay than fruits and seeds. All the three parts of the plant showed considerable a-amylase inhibitory activities but the leaves proved to be much stronger than fruits and seeds; their IC50 values being 5.03, 79.92 and 80.07 mg/mL respectively; while that of acarbose standard it was 1.20 mg/mL. Antimicrobial activities of leaves, fruits and seeds were investigated against Salmonella typhi, Escherichia coli, Bacillus subtilis, Shigella sonnei, Staphylococcus aureus and Pseudomonas aeruginosa. The antimicrobial activities of leaves against different microorganisms were in general better than those of fruits and seeds. However, fruits showed remarkable efficacy against S. typhi which was almost equal to antibiotic cefixime and clarithromycin.